Extracorporeal Liver Support and Liver Transplant for Patients with Acute-on-Chronic Liver Failure - Li, Han; Chen, Harvey Shi-Hsien; Nyberg, Scott L. (Seminars in Liver Disease, 2016)
Recognition of acute-on-chronic liver failure (ACLF) as a unique entity is slowly evolving, as are therapies to improve survival of affected patients. Further investigation into its disease process and proper treatments with critical timing are important for improving patient survival. At this time, liver transplant is the only treatment known to improve survival in liver-failure patients. However, liver transplantation has its own disadvantages, such as organ shortage and the need for lifelong immunotherapy. Bridging therapies such as extracorporeal liver-support systems are attractive options to stabilize patients until transplantation or spontaneous recovery. The goals of these liver-support systems are to remove detoxification products, reduce systemic inflammation, and enhance regeneration of the injured liver. These devices have been under development for the past decade; a few are in clinical trials. At this time, there is no proven clearcut survival benefit in these devices, but they may improve the outcome of challenging cases and potentially avoid or postpone liver transplantation in some cases.
Keywords: acute-on-chronic liver failure; artificial liver-support systems; bioartificial liver-support systems; liver transplant